Content marketing strategy in increasing consumer interaction on social media - Ismail Razak (Sean Institute, 2024)
In this digital era, social media has become the main platform for communicating and interacting online. Therefore, content marketing strategies are crucial to attract consumer attention and build sustainable engagement. This research aims to examine and analyze the effectiveness of content marketing strategies in increasing consumer interaction on social media. This research uses a qualitative approach with descriptive methods. The research results show that an effective content marketing strategy on social media requires a deep understanding of the audience, branding consistency, and a balance between content frequency and quality. Responsiveness to audience comments, collaboration with others, and continuous evaluation through analytical tools form key pillars in improving consumer engagement. In conclusion, content marketing success on social media involves an adaptive approach, leveraging technology, and keeping up with emerging trends to build solid relationships with audiences and achieve marketing goals.